COVID-19 MORTALITY IN BELGRADE - Rosić, Nataša; Šantrić Milićević, Milena (Srpski medicinski časopis Lekarske komore, 2021)
Summary The most valid data on Kovid-19 are data on mortality, because they show how many precious lives it took, that is, how much this disease has taken hold in one country. This data is valuable for analysis and comparison and can inform health care decision makers. This paper presents the basic characteristics of mortality from Kovid-19 in Belgrade in 2020. It was noticed that the Kovid-19 pandemic took 0.2% of people, and the majority of deaths were made up of a male contingent of residents. The results indicate a significant premature mortality that could have been avoided, as many studies have so far shown benefits from the application of protection, prevention and disease control measures. It remains to be determined in other studies how many years of life were lost due to premature mortality in connection with the Kovid-19 pandemic in Belgrade. This research provides evidence that can enrich the discussion and conclusions about the losses due to the Kovid-19 pandemic at the international level. Key words: mortality rates, Kovid-19, causes of death, Serbia